Sustainable building materials (SBMs) and their impact on displaced persons health/wellbeing in selected IDP facilities, Nigeria - Ekhaese, Eghosa N.; Akindoyin, Praise O.; Mohammed, Ibrahim A. (Frontiers in Materials, 2024)
There are 70.8 million Internally Displaced Persons (IDPs) in the world. In Sub-Saharan Africa (SSA), Nigeria has 16.5 million people and the highest displacement rate. IDPs in Nigeria need shelters primarily to mitigate homelessness and improve their quality of health through sustainable building materials (SBM) used in design and construction. The study aimed to investigate SBMs and their impact on the health/well-being of Displaced Persons in IDP facilities to promote the health benefits of SBMs. Assess the SBMs used to design IDP facilities in the three case studies; ascertain the health/well-being components of the SBMs; and analyse the impact of SBM on displaced persons’ health/well-being. The study used the mixed (quality and quantitative) research method while leveraging the case study design. The research philosophy is pragmatism, and the research paradigms are interpretivist and constructivist. The data collection instrument includes a questionnaire survey for quantitative data, an in-depth interview (IDI) guide, and an observation schedule (direct and participant). The findings reveal that SBMs have some health benefits, SBMs have impacts on the IDPs’ well-being, and SBMs can be sourced locally. According to the study, SBMs can reflect the people’s culture, making IDPs homely, happy and comfortable with positive psychosocial impacts that may improve their mental health.